2004
DOI: 10.1175/1520-0450(2004)043<0487:dgefot>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Deducing Ground-to-Air Emissions from Observed Trace Gas Concentrations: A Field Trial

Abstract: Inverse-dispersion techniques allow inference of a gas emission rate Q from measured air concentration. In "ideal surface layer problems," where Monin-Obukhov similarity theory (MOST) describes the winds transporting the gas, the application of the technique can be straightforward. This study examines the accuracy of an ideal MOST-based inference, but in a nonideal setting. From a 6 m ϫ 6 m synthetic area source surrounded by a 20 m ϫ 20 m square border of a windbreak fence (1.25 m tall), Q is estimated. Open-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
209
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 306 publications
(240 citation statements)
references
References 23 publications
5
209
0
1
Order By: Relevance
“…Laser-based criteria are applied to remove potentially inaccurate or unrepresentative line averaged concentration values, especially when observations correspond to <5 min of a 10-min period, R 2 min (a measure of observed concentration relative to internal cell reference) is <98, and/or when reported light levels (an operating, unitless parameter related to the signal level of the returning laser beam) falls outside an operating range; 3000 to 11 000. Criteria applied to the BLS output, intended to remove error-prone periods, have been applied in previous studies and are based on low wind speed periods (Flesch et al, 2014), periods of extreme atmospheric stratification (Flesch et al, 2004), where actual wind conditions violate WindTrax assumptions, and/or when the fractional coverage (footprint) of the downwind OPL measurement relative to the source area is marginal (Flesch et al, 2007). The application of the criteria removes outliers in the emission dataset (WindTrax output) unique to location and conditions during measurement periods.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Laser-based criteria are applied to remove potentially inaccurate or unrepresentative line averaged concentration values, especially when observations correspond to <5 min of a 10-min period, R 2 min (a measure of observed concentration relative to internal cell reference) is <98, and/or when reported light levels (an operating, unitless parameter related to the signal level of the returning laser beam) falls outside an operating range; 3000 to 11 000. Criteria applied to the BLS output, intended to remove error-prone periods, have been applied in previous studies and are based on low wind speed periods (Flesch et al, 2014), periods of extreme atmospheric stratification (Flesch et al, 2004), where actual wind conditions violate WindTrax assumptions, and/or when the fractional coverage (footprint) of the downwind OPL measurement relative to the source area is marginal (Flesch et al, 2007). The application of the criteria removes outliers in the emission dataset (WindTrax output) unique to location and conditions during measurement periods.…”
Section: Resultsmentioning
confidence: 99%
“…(Flesch et al, 2004 and. In these studies it was assumed that the area represented a uniform source of CH 4 ( Figure 2).…”
Section: Methodsmentioning
confidence: 99%
“…The bLS technique uses the backward Lagrangian stochastic dispersion model for inversely calculating emissions from distributed sources [6]. The software Wintrax 2.0, a window-based bLS computer program developed by Thunder Beach Scientific [7] was used in this study.…”
Section: It Requires Knowledge Of the Tracer Concentration And Wind Fmentioning
confidence: 99%
“…The low 86% recovery of CH 4 was attributed to the presence of cattle (area source) confounding CH 4 point source release. Previous release and recovery work by Flesch et al (2004), using an open-path laser, found that the BLS recovered 102% of the controlled release. Harper et al (2010) looked at a number of release/ recovery BLS studies and concluded the BLS accuracy was 100 6 10%.…”
Section: Accuracy Of Micrometeorological Techniquesmentioning
confidence: 93%